1983
DOI: 10.1136/oem.40.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of vibration syndrome in response to total hand-tool operating time.

Abstract: The correlation between the severity of vibration syndrome and hand-tool operating time in chain saw workers has been studied. The total chain saw operating time was calculated by using the equation: chain saw operating hours/day x days/year x years, and 266 chain saw operators were classified into four groups (0-2000 h, 2000-5000 h, 5000-8000 h, over 8000 h). Forty-six forestry workers not using chain saws were used as controls. The prevalence rates of symptoms were checked and statistically compared in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…It is a well-known fact that WF episodes are manifested or occur when the temperature is low, because low temperature significantly influences peripheral blood Burström et al circulation (10,11). One reason for our finding could be that the symptoms are more easily provoked in cold climate (ie, if the HAV-exposed workers living in the south had lived in the north they should have reported WF to the same extent).…”
Section: Discussionmentioning
confidence: 62%
“…It is a well-known fact that WF episodes are manifested or occur when the temperature is low, because low temperature significantly influences peripheral blood Burström et al circulation (10,11). One reason for our finding could be that the symptoms are more easily provoked in cold climate (ie, if the HAV-exposed workers living in the south had lived in the north they should have reported WF to the same extent).…”
Section: Discussionmentioning
confidence: 62%
“…M iya shita et al (12) ha ve reported on the relationship be tween the progress o f th e vibra tion syndro me and the tota l chain-saw operating t im e among forestry wor kers. They show ed th at a group wit h 2 000 to 5 000 h of cha in-saw operation had peripheral ne rve a nd circulatory d isturba nces, including Ra ynaud' s ph enomenon, while even the group with less than 2 000 h of expe rience complain ed of ti ng ling, numbness, o r pain and that the group with over 5 000 h of exposure su ffered severe functional , o r o rganic changes owing to vibration.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that long-term exposure to hand-transmitted vibration causes reduced grip strength and intrinsic muscular dysfunction [16][17][18] . Biopsies from the abductor pollicis brevis muscle in vibration-exposed workers have shown malalignment of myofibrils 19) .…”
Section: Discussionmentioning
confidence: 99%